Implementation of Early Education with the Mbolo Weki Method as a Policy Support for Early Detection of DM in the Community - Abdul Haris; Rizki Aditya (Postgraduate, University of Mataram, 2025)
The application of the Mbolo Weki method in early education has significant potential in supporting early detection of Diabetes Mellitus (DM) in the community. This study used a quasi-experimental method in Bima Regency, West Nusa Tenggara, on a population at risk of diabetes mellitus. The study subjects consisted of 120 individuals aged 30 years and above who were selected through a cluster random sampling technique. Data collection instruments included a questionnaire and a digital blood sugar monitor, as well as a community participation observation sheet. Data were analyzed using descriptive tests, normality tests, paired t-tests, and chi-square tests to assess differences and relationships between variables. The results showed that the increase in blood sugar checking behavior was also significant, with the intervention group showing an increase from 20% to 72%, while the control group only experienced an increase from 18% to 30%. The significant reduction in participants with blood sugar values ≥ 200 mg/dl in the intervention group (from 25% to 13%) compared to the control group (from 23.30% to 21.7%) further strengthens the effectiveness of this method. Statistical analysis using the t-test and chi-square test showed a p-value < 0.001, indicating a significant relationship between the education received and behavior change.